2016
DOI: 10.7554/elife.20145
|View full text |Cite
|
Sign up to set email alerts
|

A conserved bacterial protein induces pancreatic beta cell expansion during zebrafish development

Abstract: Resident microbes play important roles in the development of the gastrointestinal tract, but their influence on other digestive organs is less well explored. Using the gnotobiotic zebrafish, we discovered that the normal expansion of the pancreatic β cell population during early larval development requires the intestinal microbiota and that specific bacterial members can restore normal β cell numbers. These bacteria share a gene that encodes a previously undescribed protein, named herein BefA (β Cell Expansion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
115
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(121 citation statements)
references
References 73 publications
5
115
0
1
Order By: Relevance
“…However, beyond these relatively reductionist experimental approaches, we have seen an increased role of stochastic effects, from the potentially random influence of population bottlenecks during the initial colonization of the intestine [12], to the importance of passive bacterial transmission in determining the overall composition of intestinal microbiota [32,34]. Furthermore, where fine scale gnotobiotic studies have identified specific bacterial factors inducing changes in zebrafish hosts [5,79,11], broader scale studies can inform the circumstances under which those interactions even have the potential to occur (for example, by determining whether or not the bacterium is even able to colonize a zebrafish [17]), and to what degree the overall effect on the host can be predicted by the population size of individual bacterial species [18,19]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, beyond these relatively reductionist experimental approaches, we have seen an increased role of stochastic effects, from the potentially random influence of population bottlenecks during the initial colonization of the intestine [12], to the importance of passive bacterial transmission in determining the overall composition of intestinal microbiota [32,34]. Furthermore, where fine scale gnotobiotic studies have identified specific bacterial factors inducing changes in zebrafish hosts [5,79,11], broader scale studies can inform the circumstances under which those interactions even have the potential to occur (for example, by determining whether or not the bacterium is even able to colonize a zebrafish [17]), and to what degree the overall effect on the host can be predicted by the population size of individual bacterial species [18,19]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition to inducing changes in the intestinal track and the immune system, both of which come into frequent contact with microorganisms and microbial products, there is mounting evidence of microorganism-dependent impacts on the development of other organs. For example, our group found that microbiota are required for normal expansion of pancreatic β-cells in larval zebrafish and we discovered a single protein produced by specific zebrafish gut bacteria that is sufficient for this expansion in germ-free larvae [11]. Furthermore, homologs of this protein, which we named Beta cell expansion factor A or BefA, are found in microorganisms isolated from human microbiota and show a similar ability to induce β-cell expansion in zebrafish, suggesting this function has a conserved origin.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish physiology and metabolism display extensive conservation with humans and other mammals. This permits the zebrafish to effectively model key pathophysiological processes involved in human diseases such as inflammatory bowel disease, insulin resistance, diabetes, hepatic steatosis, dyslipidemia, atherosclerosis, and obesity (Hill et al, 2016; Marjoram and Bagnat, 2015; Renshaw and Trede, 2012; Schlegel and Gut, 2015). In addition to identification of novel disease genes and therapies, these models can be used to define the physiologic function of genes implicated by genome-wide association studies in humans (Minchin et al, 2015).…”
Section: The Pathophysiological Zebrafishmentioning
confidence: 99%
“…Colonization of gnotobiotic zebrafish with simple defined bacterial communities revealed that specific host responses can be determined by community composition, but that the relative abundance of a community member does not necessarily predict its relative impact (Rolig et al, 2015). Gnotobiotic zebrafish can be used to discover novel microbial products that control important aspects of host physiology, as recently demonstrated in the identification of a conserved bacterial protein that promotes pancreatic β-cell number (Hill et al, 2016). Evidence for microbial control of zebrafish physiology is also derived from studies in which administration of probiotic bacteria to zebrafish altered behavior, growth bone and metabolic biomarkers (Borrelli et al, 2016; Falcinelli et al, 2015).…”
Section: The Pathophysiological Zebrafishmentioning
confidence: 99%
“…Early studies of germ-free zebrafish highlighted that the microbiota had a conserved role in the growth and maturation of the intestine (Bates et al, 2006; Rawls et al, 2004). Now, in eLife, Karen Guillemin of the University of Oregon and colleagues – Jennifer Hampton Hill (Oregon), Eric Franzosa and Curtis Huttenhower, both of Harvard and the Broad Institute – have used these tools to reveal that microbiota-host interactions could play a role in the development of beta (β) cells in the pancreas (Hill et al, 2016). …”
mentioning
confidence: 99%